2007
DOI: 10.1177/1533317507299771
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Dementia: Do Professional Caregivers Focus on the Significant Domains?

Abstract: The domains of quality of life that are considered important by people with dementia and professional caregivers are not in agreement. This explorative study addresses the question, "To what degree do professional caregivers, in their daily working routine, focus on the quality-of-life domains that people with dementia consider essential?" Study participants were nursing assistants who work in 24-hour nursing home care and professionals who offer daytime activities. Three hundred and seventy-four caregivers wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
(18 reference statements)
0
20
0
2
Order By: Relevance
“…In theories specifically directed at people with dementia, occupation is assumed to be important to feel useful, maintain self-esteem, for feelings of belonging, sense of aesthetics and maintenance of abilities (Brod, Stewart, Sands & Walton, 1999;Lawton, 1994). Several study results from in-depth interviews with people with dementia, residing in the community as well as in long-term care facilities, confirm these theoretical assumptions (Cahill & Diaz-Ponce, 2011;Clare, Rowlands, Bruce, Surr, & Downs, 2008;Gerritsen et al, 2007;Orrell et al, 2008;Phinney, Chaudhury & O'connor, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…In theories specifically directed at people with dementia, occupation is assumed to be important to feel useful, maintain self-esteem, for feelings of belonging, sense of aesthetics and maintenance of abilities (Brod, Stewart, Sands & Walton, 1999;Lawton, 1994). Several study results from in-depth interviews with people with dementia, residing in the community as well as in long-term care facilities, confirm these theoretical assumptions (Cahill & Diaz-Ponce, 2011;Clare, Rowlands, Bruce, Surr, & Downs, 2008;Gerritsen et al, 2007;Orrell et al, 2008;Phinney, Chaudhury & O'connor, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…In part, this was linked to having a sense of being useful. Interestingly, Dröes et al (2006) point out that being of use was not mentioned by carers as being relevant to quality of life and Gerritsen et al (Gerritsen et al, 2007) found that professional carers only focused on it to a minor degree. The importance of feeling useful and being able to give something back runs counter to the common perception of people with dementia as being unable or unwilling to reciprocate, which was one of the frames identified by van .…”
Section: Perceptions Of People With Dementia Themselvesmentioning
confidence: 99%
“…Although dementia and QoL has received much research attention over recent years (Dro¨es et al, 2006;Ettema et al, 2005;Gerritsen et al, 2007;Selai & Trimble, 1999), there is still no universal definition of QoL; nor has a gold standard been developed for its measurement. One dilemma long debated is whose views should be sought; however, in recent years, growing international evidence has accumulated demonstrating that most people with dementia (PwD) can respond well to questions asked about their QoL (Brod, Stewart, Snads, & Walton, 1999;Cahill et al, 2004;Logsdon, Gibbson, MsCurry, & Teri, 2002;Mozley et al, 1999;Ready, Ott, Grace, & Fernandez, 2002;Trigg, Jones, & Skevington, 2007) and that proxy informants, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%